Expandable Polymer Assisted Wearable Personalized Medicinal Platform. Issue 10 (9th September 2020) - Babatain, Wedyan; Gumus, Abdurrahman; Wicaksono, Irmandy; Buttner, Ulrich; El‐atab, Nazek; Rehman, Mutee Ur; Qaiser, Nadeem; Conchouso, David; Hussain, Muhammad Mustafa
Abstract: Conventional healthcare, thoughts of treatment, and practice of medicine largely rely on the traditional concept of one size fits all. Personalized medicine is an emerging therapeutic approach that aims to develop a therapeutic technique that provides tailor‐made therapy based on everyone's individual needs by delivering the right drug at the right time with the right amount of dosage. Advancement in technologies such as wearable biosensors, point‐of‐care diagnostics, microfluidics, and artificial intelligence can enable the realization of effective personalized therapy. However, currently, there is a lack of a personalized minimally invasive wearable closed‐loop drug delivery system that is continuous, automated, conformal to the skin, and cost‐effective. Here, design, fabrication, optimization, and application of a personalized medicinal platform augmented with flexible biosensors, heaters, expandable actuator and processing units powered by a lightweight battery are shown. The platform provides precise drug delivery and preparation with spatiotemporal control over the administered dose as a response to real‐time physiological changes of the individual. The system is conformal to the skin, and the drug is transdermally administered through an integrated microneedle. The developed platform is fabricated using rapid, cost‐effective techniques that are independent of advanced microfabrication facilities to expand its applications to low‐resource environments. Abstract : The presented expandable polymer assisted personalized medicinal platform is capable of providing minimally invasive closed‐loop drug preparation and delivery system that is continuous, automated, wearable, and cost effective. The platform is integrated with flexible sensors, heating elements, expandable actuator, processing unit, and lightweight battery enabling the realization of truly effective personalized therapy.